Investigation of organizational culture in companies in high rate polluted countries: Review of existing evidence and application of the new VOX Organizationis model - Ivona Mileva; Marjan Bojadjiev; Miodraga Stefanovska-Petkovska; Ana Tomovska-Misoska (University American College Skopje, 2020)
As one of the aspects of modern behavioral and economic sciences during the past few years, organizational culture has become one of the critical points in business practice. The studies has shown that organizational culture is considered to be an "asset" that can be connected to progress execution, hence being remarkable to the life of the organization. However, since the market competition rules has become more radical and demand for companies a complex "collection" of measures and changes, modern companies should focus not only on a solid organizational culture, but rather on the alignment within. Alignment along with innovativeness and integration can assist the companies in outperforming their main rivals and competitors. Therefore, numerous organizations endeavor to measure their organizational cultures through already reputable models by perceived authors or to receive inside strategies to supply understandable parameters in order to appraise their organizational culture. The process of checking alignment isn't a onetime exertion anymore, but rather it is a portion of persistent endeavors for change of the companies' required proficiency and long-term sustainability. The aim of this research is to investigate and identify the organizational culture and organizational alignment in a companies in a countries that are facing high pollution rate and check some theoretical approaches to this phenomenon. As these type of analyses, were rarely conducted in these countries, one of the objectives of this research is the practical implementation of VOX Organizationis, an instrument for measuring alignment, culture and leadership values and review of evidence and recommendation on its implementations within the companies. This study will provide the reader with a greater understanding of how and with which instrument to measure organizational culture and its alignment, through introducing up-to-date scientific research in the same field.
Keywords: 330; Vox organizations; organizational alignment; organizational culture; high-rate polluted countries